2016
DOI: 10.1007/s11103-016-0509-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel thidiazuron-derived inhibitors of cytokinin oxidase/dehydrogenase

Abstract: Two new TDZ derivatives (HETDZ and 3FMTDZ) are very potent inhibitors of CKX and are promising candidates for in vivo studies. Cytokinin hormones regulate a wide range of essential processes in plants. Thidiazuron (N-phenyl-N'-1,2,3-thiadiazol-5-yl urea, TDZ), formerly registered as a cotton defoliant, is a well known inhibitor of cytokinin oxidase/dehydrogenase (CKX), an enzyme catalyzing the degradation of cytokinins. TDZ thus increases the lifetime of cytokinins and their effects in plants. We used in silic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 53 publications
1
51
0
1
Order By: Relevance
“…The only exception to this rule is the compounds described in this work. Although many thidiazuron derivatives have been synthesized (e.g., Yip and Yang, 1986 ; Nisler et al, 2016 ), none of the compounds reported here have previously been described. All of the synthesized compounds were characterized by high resolution Mass Spectrometry and 1 H NMR (Supplementary Tables S1 , S2 ).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The only exception to this rule is the compounds described in this work. Although many thidiazuron derivatives have been synthesized (e.g., Yip and Yang, 1986 ; Nisler et al, 2016 ), none of the compounds reported here have previously been described. All of the synthesized compounds were characterized by high resolution Mass Spectrometry and 1 H NMR (Supplementary Tables S1 , S2 ).…”
Section: Resultsmentioning
confidence: 85%
“…The compound 1,2,3-thiadiazol-5-ylamine was the starting material for the synthesis of 5-isocyanato-1,2,3-thiadiazole, which was prepared as described by Nisler et al ( 2016 ). The compounds TD- t Z, TD-iP, TD-DHZ and compounds 1-15 were prepared by mixing 5-isocyanato-1,2,3-thiadiazole and the corresponding commercially available amine under mild heat (30 to 60°C) in tetrahydrofuran in the presence of a catalytic amount of triethylamine (Goldschmidt and Bardach, 1892 ).…”
Section: Methodsmentioning
confidence: 99%
“…This may be due to a number of reasons, e.g., TDZ exhibits strong CK activities in several bioassays, however in contrast to t Z, cannot be degraded by cytokinin oxidase dehydrogenase (CKX, a key enzyme involved in CK degradation in plants [56,57]). TDZ cannot be deactivated by O -glucosylation and can maintain a higher content of endogenous CKs in plant tissue by inhibiting the function of CKX [58,59,60]. Owing to its high CK and particularly antisenescence activity, TDZ has been extensively studied and used to prolong the life of cut flowers [55].…”
Section: Antisenescent Activity Of Urea Based Cks and Their Derivamentioning
confidence: 99%
“…Applying chemical defoliants before harvesting can promote the shedding of cotton leaves as well as promote boll opening and thus effectively reduce the content of impurities in raw cotton and enhance the harvest efficiency, especially for the mechanically harvested cotton [25,27]. Thidiazuron (a synthetic cytokinin-like molecule, TDZ) is the main component of cotton chemical defoliants that widely used in most cotton-producing countries currently [28]. However, the mechanism of TDZ inducing cotton leaf shedding is not completely clear.…”
mentioning
confidence: 99%